2020
DOI: 10.3390/ijms21218312
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils as a Novel Target of Modified Low-Density Lipoproteins and an Accelerator of Cardiovascular Diseases

Abstract: Neutrophil extracellular traps (NETs) significantly contribute to various pathophysiological conditions, including cardiovascular diseases. NET formation in the vasculature exhibits inflammatory and thrombogenic activities on the endothelium. NETs are induced by various stimulants such as exogenous damage-associated molecular patterns (DAMPs). Oxidatively modified low-density lipoprotein (oxLDL) has been physiologically defined as a subpopulation of LDL that comprises various oxidative modifications in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 139 publications
0
11
0
1
Order By: Relevance
“…35 Oxidatively modified low-density lipoprotein also plays an important role in atherosclerosis through foam cell formation, enhancing NET-mediated inflammatory responses in vascular cells through neutrophil activation. 36 Previous reports indicated that neutrophils are strongly associated with in-hospital mortality and major adverse cardiovascular and cerebrovascular events. 37 A lower lymphocyte count was associated with atherosclerosis progression and adverse clinical outcomes in patients with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…35 Oxidatively modified low-density lipoprotein also plays an important role in atherosclerosis through foam cell formation, enhancing NET-mediated inflammatory responses in vascular cells through neutrophil activation. 36 Previous reports indicated that neutrophils are strongly associated with in-hospital mortality and major adverse cardiovascular and cerebrovascular events. 37 A lower lymphocyte count was associated with atherosclerosis progression and adverse clinical outcomes in patients with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…NETs induce oxidative stress leading to oxidization of HDL particles, thereby reducing their beneficial cholesterol efflux ability ( 176 ). In addition, NETs contain myeloperoxidase, which has the potential to modulate LDL oxidation ( 177 , 178 ). In humans, inflammasome activation and NETosis may result in atherosclerotic plaque erosion and thrombosis, especially in patients with T2DM, clonal hematopoiesis or chronic kidney disease ( 179 ).…”
Section: Current Perspectives and Limitationsmentioning
confidence: 99%
“…Oxidized low-density lipoprotein (oxLDL), which easily accumulates in macrophages, is used as an atherosclerosis-inducing molecule. Many studies have shown that it stimulates neutrophils to form NETs ( 33 ). The specific deletion of peptidyl arginine deiminase-4 (PAD4) reduces the formation of NETs and significantly alleviates atherosclerosis, complications, and inflammation caused by macrophages ( 34 , 35 ).…”
Section: The Role Of Nets In Atherosclerosis and Arterial Thrombosismentioning
confidence: 99%